Pfeiffer Country : The Tenant Farms and Business Activities of Paul Pfeiffer in Clay County, Arkansas, 1902-1954 - Laymon, Sherry (Book collections on Project MUSE., 2009)
Clay County, Arkansas, was a flatland with little improvements at the outset of the twentieth century. Into this primitive society came a St. Louis entrepreneur with a liking for agriculture. Paul Pfeiffer bought large tracts of land, set up tenant farmers, and reigned for nearly fifty years as a beneficent landlord. Laymon records the gratitude of many a family who remember with appreciation loans made to acquire equipment. When farming was interrupted by the coming of the railroad, both Pfeiffer and his tenants adapted to a lumbering economy-so long as the hardwood forest lasted. Interesting.